O Sofrimento: uma análise antropológica - Lopes, Eugénio (Gregorianum, 2024)
When we speak about the human person, we should also speak of affectivity, a component that is equally essential for self-realization. The affective map of the human person is very vast and includes several affections, such as suffering. However, when approaching this affect, I think some mistakes are made from a scientific point of view, such as: a) suffering is always considered as an irrational affect; b) suffering is identified as an evil, which we must always get rid of; c) it is argued that it is always possible to eliminate all suffering; d) suffering is confused with other affections, which are essentially different. In this sense, taking into account these points, I thought it would be necessary to propose a more realistic view regarding the theme of suffering. Thus, to achieve this objective, initially, I will analyze the metaphysical condition of the human person, relating it to affectivity and, in this sense, to suffering. Later, I will distinguish and relate suffering to other affects. Finally, I will analyze the two types of suffering, how we should relate to them, and how they can be evaluated from a moral point of view.